2021
DOI: 10.18400/tekderg.590356
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Two Vegetation Indices (NDVI and VCI) Over Asi Basin in Turkey

Abstract: Climate change and global warming are among the issues that humanity is most concerned about the future. The growing drought and flood risks that increase despite the taken measures have led to the adoption of an integrated understanding on the topic of water management in recent years. To manage the increased risk of drought and to make sustainable planning, the dimensions of drought should be known first. For this purpose, many drought indices have been developed. The Normalized Difference Vegetation Index (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…The study in which the vegetation index was associated with precipitation (Şahin et al, 2009) showed a correlation between the data obtained from the precipitation stations in different regions of Turkey and the NDVI data. Similar studies performed with data for rainfall monitoring stations in Turkey and compliance with the drought indices data were discussed (Dikici, 2013, Dikici & Aksel, 2021. NDVI is one of the vegetation indices that is quite widely used in forest classi cation and agricultural studies as well as in the detection of the change in land cover.…”
Section: Remote Sensing and Data Sourcesmentioning
confidence: 75%
“…The study in which the vegetation index was associated with precipitation (Şahin et al, 2009) showed a correlation between the data obtained from the precipitation stations in different regions of Turkey and the NDVI data. Similar studies performed with data for rainfall monitoring stations in Turkey and compliance with the drought indices data were discussed (Dikici, 2013, Dikici & Aksel, 2021. NDVI is one of the vegetation indices that is quite widely used in forest classi cation and agricultural studies as well as in the detection of the change in land cover.…”
Section: Remote Sensing and Data Sourcesmentioning
confidence: 75%
“…The impact of agricultural drought on crops is difficult to detect directly by NDVI [36], [37]. The VCI calculated based on NDVI can monitor local differences in ecosystem productivity [21].…”
Section: A Normalized Remote Sensing Data 1) Vcimentioning
confidence: 99%
“…Many remote sensing-based drought indices have been established, and NVDI is the most widely used [45]- [48]. Besides, Vegetation Condition Index (VCI) calculated based on NDVI has also been applied to global and regional agricultural drought monitoring [49]- [52]. Different values of VCI represents different drought conditions.…”
Section: A Calculation Of Scaled Sif Indexmentioning
confidence: 99%
“…VCI can be used as an index for agricultural drought monitoring [49]- [52]. After the agricultural area was extracted, the monthly average SIF index and VCI value of agricultural area from 2000 to 2017 were calculated.…”
Section: G Correlation Analysis With Vcimentioning
confidence: 99%